Revisiting the Muscles and Nerves of Anterior Compartment of the Arm: A Case Report - Busra ANACUR; Eren OGUT; Cagatay BARUT (Medeniyet Medical Journal)
During routine dissection of the anterior compartment of the arm region, we encountered several variations in the muscular and neural structures in the right upper extremity of a female cadaver. We observed one superiorly positioned extramuscular head with fibers originating from both the biceps brachii (BB) and coracobrachialis (CB) muscles and one inferiorly positioned extramuscular head with fibers solely from the BB muscle. The musculocutaneous nerve did not penetrate the CB muscle, but instead provided a muscular branch that communicated with the median nerve (MN). Both the MN and brachial artery (BA) flow beneath the extra head. This case suggests that the described variations may contribute to the entrapment of the MN and compression of the BA. Understanding these variations is crucial before surgical intervention. The failure to recognize such anatomical nuances could lead to inadvertent nerve injury or compromised vascular perfusion, emphasizing the need for preoperative planning and intraoperative vigilance.